Challenges in Drafting Village Regulations in Nggawia Village - Albert Morangki; Erwin Taroreh; Jemmy Dedi Rengku (IHSA Institute, 2026)
Village Regulations (Perdes) are important legal instruments in the administration of village governance because they function as the legal basis for regulating village community life. This study aims to analyze the stages of forming Village Regulations based on statutory provisions and to examine the obstacles faced by the Village Government and the Village Consultative Body (BADAN PERMUSYAWARATAN DESA (BPD)) in the drafting process in Nggawia Village, Tojo Barat Subdistrict, Tojo Una-Una Regency. This research employs an empirical juridical legal research method with a sociological approach. Data were collected through interviews, field observations, and document studies, and were analyzed using descriptive qualitative analysis. The results show that, normatively, the stages in the establishment of village regulations has been systematically regulated in Law Number 6 of 2014 on Villages and Minister of Home Affairs Regulation Number 111 of 2014, which include the stages of planning, drafting, discussion, enactment, promulgation, and dissemination. However, in practice in Nggawia Village, this process has not been carried out optimally. Internal constraints include the limited legal understanding and technical competence of village officials and Badan Permusyawaratan Desa (BPD) members, as well as the high turnover of village apparatus. External constraints include the suboptimal guidance, assistance, and supervision from the regional government, limited technical facilitation, and low levels of community participation. These conditions have affected the quality and quantity of Village Regulations produced. This study recommends strengthening the capacity of village officials, enhancing the role of regional government guidance, and optimizing community participation in the promulgation of Village Regulations